2020
DOI: 10.1111/hex.13067
|View full text |Cite
|
Sign up to set email alerts
|

The reported impact of public involvement in biobanks: A scoping review

Abstract: Background Biobanks increasingly employ public involvement and engagement strategies, though few studies have explored their impact. This review aims to (a) investigate how the impact of public involvement in biobanks is reported and conceptualized by study authors; in order to (b) suggest how the research community might re‐conceptualize the impact of public involvement in biobanks. Methods A systematic literature search of three electronic databases and the INVOLVE Evidence Library in January 2019. Studies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…A positive image of biobanks is essential and therefore we recommend improving the interaction with and the awareness of the general public and other stakeholders about the scientific and societal value of biobanks and related research. This is in line with the increased focus on public involvement 76 and return of results. 77 Furthermore, to better determine biobank value, both biobanks and involved stakeholders should shift their focus from internal biobank measures toward biobank output.…”
Section: Recommendations For Creating the Right Conditions For Sustainable Biobankingsupporting
confidence: 70%
“…A positive image of biobanks is essential and therefore we recommend improving the interaction with and the awareness of the general public and other stakeholders about the scientific and societal value of biobanks and related research. This is in line with the increased focus on public involvement 76 and return of results. 77 Furthermore, to better determine biobank value, both biobanks and involved stakeholders should shift their focus from internal biobank measures toward biobank output.…”
Section: Recommendations For Creating the Right Conditions For Sustainable Biobankingsupporting
confidence: 70%
“…However, within cohort studies involving healthy participants, engagement can sometimes be omitted from study plans, partly due to a lack of recognition of its importance and partly due to a perception that it is resource intensive (financial and time) [ 2 , 6 ]. In current practice different organisations use the term engagement differentially and ambiguously [ 17 ]. Recently, studies have been conducted on cohort studies’ recruitment and retention strategies [ 2 ], however these have not reported on the participants’ experiences of their own engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, the results presented here are also aimed at providing a data-backed and evidenced theoretical underpinning for participants’ engagement in cohort studies. The persisting ambiguity and need for theorisation and conceptualisation of participant engagement is an on-going gap in practice [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, the results presented here are also aimed at providing a data-backed and evidenced theoretical underpinning for participants' engagement in cohort studies. The persisting ambiguity and need for theorisation and conceptualisation of participant engagement is an on-going gap in practice [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, within cohort studies involving healthy participants, engagement can sometimes be omitted from study plans, partly due to a lack of recognition of its important and partly due to a perception that it is resource intensive ( nancial and time) [6,2]. In current practice different organisations use the term engagement differentially and ambiguously [13]. Recently, studies have been conducted on cohort studies' recruitment and retention strategies [2], however these have not reported on the participants' experiences of their own engagement.…”
Section: Introductionmentioning
confidence: 99%